The Roles of Female Members of the House of Representatives (DPRD) on Formulation of Gender Responsive Policy in Malang City - Septy Amelia Nur Talitha; Bambang Santoso; Wike Wike (Wacana Journal of Social and Humanity Studies, 2018)
The government has set a 30% quota of women's representation in the legislature, including Malang City. The existence of women's representation to see women's participation in politics, as well as their role in making gender responsive policy. The policy formulation model used is Easton's 'political system'. The objectives of this research are: 1) to analyze the role of female parliamentarians in the formulation of gender responsive policies. 2) to describe supporting factors and inhibiting factors in the formulation of gender responsive policies. The method used in this research is qualitative with descriptive research type. Data collection was done by observation and interview technique. Source of data comes from primary data and secondary data. The result of the research shows that women representation in DPRD Malang is not maximal, their role in initiating gender responsive policy is still lacking, but in the outside they still have concern especially protection for victims of violence of woman and child.